On Paul Ricoeur : narrative and interpretation - Wood, David, 1946- (Warwick studies in philosophy and literature., 1991)
This book examines the later work of Paul Ricoeur, particularly his major work, Time and Narrative . The essays, including three pieces by Ricoeur himself, consider this important study, extending and developing the debate it has inspired. Time and Narrative is the finest example of contemporary philosophical hermeneutics and is one of the most significant works of philosophy published in the late twentieth century. Paul Ricoeur's study of the intertwining of time and narrative proposes and examines the possibility that narrative could remedy a fatal deficiency in any purely phenomenological approach. He analysed both literary and historical writing, from Proust to Braudel, as well as key figures in the history of philosophy: Aristotle, Augustine, Kant, Hegel, Husserl and Heidegger. His own recognition of his limited success in expunging aporia opens onto the positive discovery of the importance of narrative identity, on which Ricoeur writes here. Other contributors take up a range of different topics: Tracing Ricoeur's own philosophical trajectory; reflexively applying the narrative approach to philosophy, or to his own text; reconstructing his dialectic of sedimentati and tradition. An essential companion to Time and Narrative, this collection also provides an excellent introduction to Ricoeur's later work and to contemporary works in philosophical hermeneutics.